Bioresorbable Scaffolds: Current Technology and Future Perspectives - Forrestal, Brian (Rambam Maimonides Med J, 2020)
Metallic drug-eluting stents have led to significant improvements in clinical outcomes but are inherently limited by their caging of the vessel wall. Fully bioresorbable scaffolds (BRS) have emerged in an effort to overcome these limitations, allowing a “leave nothing behind” approach. Although theoretically appealing, the initial experience with BRS technology was limited by increased rates of scaffold thrombosis compared with contemporary stents. This review gives a broad outline of the current BRS technologies and outlines the refinements in BRS design, procedural approach, lesion selection, and post-procedural care that resulted from early BRS trials.